2020
DOI: 10.1097/wnr.0000000000001370
|View full text |Cite
|
Sign up to set email alerts
|

Immunopotentiator thymosin alpha-1 attenuates inflammatory pain by modulating the Wnt3a/β-catenin pathway in spinal cord

Abstract: The mechanism of inflammatory pain involves the central nervous system (CNS) and the immune system. It is reported that immunopotentiator thymosin alpha-1 (Tα1) can reduce inflammation, protect neurons and strengthen the immune function. However, the roles of Tα1 in inflammatory pain still remain unclear. In this study, we found Tα1 can attenuate the complete Freund’s adjuvant (CFA)-induced mechanical allodynia and heat hyperalgesia. Meanwhile, it reduced the upregulation of CFA-induced inflammatory mediators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Thymus epithelial cells and their secreted thymosin and thymosin are the main components of the thymic microenvironment, which allow thymocytes to migrate and interact with each other, helping thymocytes to develop and mature, and both of them can promote the differentiation of thymocytes [13] .However, cytokines secreted by thymus epithelial cells and hormone-mediated signal transduction showed a decreasing trend during aging.The experimental results showed that thymosin α and thymosin were increased in the thymus of aging macaques after the infusion of bone marrow mesenchymal stem cells, which proved that BMSCs can improve the secretion function of thymus [14] and enhance the immune function [15,16] , and play an important role in maintaining the homeostasis of the microenvironment of thymus.…”
Section: Discussionmentioning
confidence: 99%
“…Thymus epithelial cells and their secreted thymosin and thymosin are the main components of the thymic microenvironment, which allow thymocytes to migrate and interact with each other, helping thymocytes to develop and mature, and both of them can promote the differentiation of thymocytes [13] .However, cytokines secreted by thymus epithelial cells and hormone-mediated signal transduction showed a decreasing trend during aging.The experimental results showed that thymosin α and thymosin were increased in the thymus of aging macaques after the infusion of bone marrow mesenchymal stem cells, which proved that BMSCs can improve the secretion function of thymus [14] and enhance the immune function [15,16] , and play an important role in maintaining the homeostasis of the microenvironment of thymus.…”
Section: Discussionmentioning
confidence: 99%
“…However, without any doubt, Tα1 is an important immune modulator [105,106], which also exerts actions in the CNS, which seem to be partially due to immunological influences on neuroplasticity [107,108].…”
Section: Thymosinmentioning
confidence: 99%